Nurse Management and Leadership Practices in Hospitals: A Systematic Review - Ayu Trisnadewi; Elsye Maria Rosa (Indonesian Journal of Global Health Research, 2026)
Nurse management and leadership play a critical role in shaping nurses’ work environments, patient safety, and organizational performance in hospital settings. In recent years, there has been a growing shift from traditional hierarchical management toward more relational and clinically oriented leadership practices. However, empirical evidence regarding dominant leadership styles, associated outcomes, and remaining research gaps remains dispersed across the literature. This systematic review aimed to synthesize existing evidence on nurse management and leadership practices in hospital settings, with a focus on dominant leadership styles, reported outcomes, and identified research gaps. A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed in PubMed/MEDLINE, Scopus, and CINAHL databases. A total of 524 articles were initially identified. After removal of duplicates and screening of titles and abstracts, 45 articles were assessed for full-text eligibility. Ten studies met all inclusion criteria and were included in the final synthesis. Data were analyzed using a narrative thematic approach. The synthesis revealed three main themes. First, transformational leadership emerged as the most frequently examined leadership style in nurse management, with increasing attention to clinical leadership among bedside nurses. Second, leadership practices were associated with nurse-related outcomes (work engagement, reduced burnout, and job performance), patient-related outcomes (quality of care, patient safety, and satisfaction), and organizational outcomes (innovative work behavior and reduced counterproductive behaviors). Third, several research gaps were identified, including the predominance of cross-sectional designs, reliance on self-reported measures, limited multicultural perspectives, and insufficient evidence on the long-term impact of leadership during and after healthcare crises such as the COVID-19 pandemic. Evidence from this systematic review indicates that relational and transformational leadership practices are consistently associated with positive outcomes for nurses, patients, and healthcare organizations in hospital settings. Strengthening leadership development and advancing longitudinal and intervention-based research are essential to better understand causal mechanisms and support sustainable improvements in nursing management and leadership.